Acylglycine Analysis by Ultra‐Performance Liquid Chromatography‐Tandem Mass Spectrometry (UPLC‐MS/MS). Issue 4 (26th April 2023) - Hobert, Judith A.; Guymon, Rebecca; Yuzyuk, Tatiana; Pasquali, Marzia
Abstract: Quantitative analysis of urine acylglycines has shown to be a highly sensitive and specific method with proven clinical utility for the diagnosis of several inherited metabolic disorders including: medium chain acyl‐CoA dehydrogenase deficiency, multiple acyl‐CoA dehydrogenase deficiency, short chain acyl‐CoA dehydrogenase deficiency, 3‐methylcrotonyl‐CoA carboxylase deficiency, 2‐methylbutyryl‐CoA dehydrogenase deficiency, isovaleric acidemia, propionic academia, and isobutyryl‐CoA dehydrogenase deficiency. Here, a method that is currently performed using ultra‐performance liquid chromatography/tandem mass spectrometry (UPLC‐MS/MS) is described. © 2023 Wiley Periodicals LLC. Basic Protocol : Urinary acylglycine analysis by UPLC‐MS/MS Support Protocol 1 : Quality control preparation Support Protocol 2 : Internal standard (ISTD) preparation Support Protocol 3 : Standard (STD)/calibrator preparation